Kepribadian Anak Usia 5-6 Tahun Berdasarkan Analisa Pendekatan Belajar Behaviorisme - Ni Made Sulastri (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
The world of education has developed various types of learning theories that are considered appropriate to the needs of students, behaviorist theory is considered the oldest theory or theory that is considered ancient. But in reality, behaviorist theory learning is still widely applied in Educational Institutions in Indonesia, because learning with a behaviorist theory approach is considered to be able to have a positive impact on child development. This theory is also increasingly developing into new theories and is considered better in its application in school institutions. Behaviorism theory views personality as a result of the interaction of individuals with their environment. This study aims to identify personality through analysis of observed behavior patterns and the influence of external factors. Using semi-structured interview methods and observations, this study reveals how the environment affects individual responses. The results of the study show that children's personalities are greatly influenced by examples of behavior that support the child's environment, habits that are formed through reinforcement and punishment.